The Main Features of Corporate Training in The Modern World - Juraev Nurmakhamad; Abdullajonova Nurzoda (Genius Journals, 2023)
This article provides information on the importance of determining the need for this process at the level of the organization, division and specific employees, as well as implementing measures to motivate them to learn when designing an employee training system. It is also noted that in training employees of an organization, it is important not only training, but also the development of employees using the principles of coaching.
Keywords: development; coaching; organization; important